Induced-feeding bioassays for detection of Bacillus thuringiensis insecticidal activity against Epilachna paenulata (Coleoptera) - Sauka, Diego Herman; Monella, Rodrigo Horacio; Benintende, Graciela Beatriz (Pesquisa Agropecuaria Brasileira, 2011)
<span style="background-color: #fff;" title="Se presenta el establecimiento de una clase nueva de bioensayos llamados de alimentación inducida." onmouseover="this.style.backgroundColor='#ebeff9'" onmouseout="this.style.backgroundColor='#fff'">The objective of this work was to establish and test the induced-feeding bioassay in order to detect Bacillus thuringiensis insecticidal activity against (Coleoptera: Coccinellidae). Larvae were induced to swallow high concentrations of spore-crystal suspensions of s Argentine B. thuringiensis strains. The great majority of strains showed no toxicity, and observed mortality was lower than 30%. Induced-feeding bioassay is feasible, and should be used for prospecting strains that produce right combinations of Cry proteins needed to an efficient pest control.